STUDI KOMPARASIKENDALI MOTOR DC DENGAN LOGIKA FUZZY METODE MAMDANI DAN SUGENO - Ibrahim Nawawi; Bagus Fatkhurrozi (Wahana Ilmuwan, 2016)
DC motors have been widely used in all fields, such as industry, household appliances, to children's toys. The main reason of the heavy use of a DC motor is the ease of control. These controllers can use analog or digital control. In this study, the method used is a DC motor control simulation with Simulink and Matlab fuzzy toolbox. The results of the simulation show that the transient response of the DC motor control using fuzzy Mamdani and Sugeno, they did not show any overshoot, steady state computing to achieve faster Sugeno Fuzzy controller with 5.4 seconds, while for fuzzy Mamdani 38.12 seconds, middle (SE) the set of fuzzy output membership of approximately 1.3, error close to zero fastest achieved by Mamdani, Sugeno while slower, Delta Mamdani fuzzy error is more stable than fuzzy Sugeno, Value steady state control signal is almost the same at 1.2.